Estudo de Sistemas Coloidais à Base de Calcogenetos de Chumbo - Gomes, Wanderson Acássio (2018)
In this study, we report on the synthesis of lead selenide (PbSe) quantum dots using an aqueous-based wet chemistry protocol. The proposed chemical route uses increasing concentration of selenium to grow the PbS shell and alloy on top of the as-precipitated PbSe core in a controllable way using 1-thioglycerol stabilizer. The concentration of selenium used was 0.1, 0.3 and 0.5 mmol, while the others one were kept fixed. The physical properties of these PbSe QDs were investigated using Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy and photoluminescence (PL) techniques. FT-IR spectra gave indication of PbSe quantum dots formation with diameters smaller than 3 nm. In addition, these spectra gave evidence of attachment of the stabilizer on the surface of the core and formation of PbSxSe1-x alloy and PbS shell. These clues are related to the displacement of the PbSe vibrational modes compared to bulk material, that confirm confinement proprieties, to the PbS vibrational modes observed and to the PbSe vibrational modes changed, respectively. In the Raman spectra the same clues were observed, confirming the results of FT-IR technique. The PL spectra corroborated with the results observed in the FT-IR and Raman spectra by identifying changes in the emission bands. It was also viewed surface defects and Pb vacancies in the PbSe and PbS formed. Therefore, based on these results, we synthesized for the first time, ultra-small PbSe QD’s via aqueous route controlling growth of PbS alloy and shell by the Se concentration during the synthesis. So, these nanostructures as-synthesized may be suitable for luminescent sensors in nanobiotechnological applications.